In Vitro Antioxidant and Anti-Denaturation Properties of Crude Arbutus Unedo L. Extracts from the Rif Region, Morocco - Benamari Omar; El yousfi Kamal; Labhar Amina; Ahidar Naoufal; Benyoub Bouchra; Elyoussfi Abdellah; Salhi Amin; Ahari M’hamed; Amhamdi Hassan (E3S Web of Conferences)
A. unedo L. is a valuable medicinal shrub with significant therapeutic properties, commonly found in Mediterranean forests with semi-arid bioclimatic conditions, traditionally used to treat various diseases, including those related to oxidative stress and infectious diseases. Hence, the present study seeks to examine the DPPH and FRAP assays, along with the anti-inflammatory activity of different extracts, by measuring absorbance using a UV-Vis spectrophotometer. The results showed that the methanol extract of A. unedo L. leaves (EMAU) exhibited the highest scavenging activity (% RSA) against the DPPH radical, with an IC50 value of 11.98 ± 1.04 µg/mL at 800 µg/mL. Whereas the ethyl acetate extract (EAAU) displayed the highest FRAP activity (1.08 ± 0.03) at 400 µg/mL. In addition, the methanol extract (EMAU) revealed superior anti-inflammatory effects, achieving 91.52 ± 0.43% inhibition at 1000 µg/mL. Based on the findings, the shrub present in the Ait Ammart area (TIZI IFRI forest) shows promising potential as a source of bioactive molecules and pharmacologically valuable metabolites.